The Influence Of Use Of A PBL Learning Model Based On The Qur'an Application Version Of The Minister Of Religion And Initial Skills On Reading Ability - Sriati Sriati (Departement of Mathematics Education, 2024)
The aim of this research is to examine the influence of using the PBL Learning Model Based on the Ministry of Religion Version of the Qur'an and Initial Ability on students' Reading Ability. This research used a True Experimental Design with a pretest-posttest control group design. The number of samples obtained was 90 students divided into 4 research classes, namely 45 students in Class 5 A and B SDLB-B as experimental samples and 45 students in Class 5 C and D SDLB-B as control samples. In carrying out statistical tests to test the hypothesis, in this case it will be carried out using the 2-way Anova analysis technique. Based on the research results, discussion and analysis results, the following conclusions can be drawn: (1) In the first hypothesis test which states: there is a difference in the increase in Reading Ability between the provision of the PBL Learning Model Based on the Qur'an Application Version of the Ministry of Religion and the Lecture Method, (2) In the second hypothesis test which states: there is a difference in the increase in Reading Ability between students who have low initial ability and students who have high initial ability, and (3) In the third hypothesis test which states: there is an interaction effect between the provision of the PBL Learning Model Based on the Qur'an Application the Ministry of Religion Version and Lecture Method and initial ability on Reading Ability, so it can be concluded that there is a positive and significant influence between the provision of the PBL Learning Model Based on the Qur'an Application Version of the Ministry of Religion and Lecture Method and initial ability on Reading Ability.